2021
DOI: 10.3390/cancers13122893
|View full text |Cite
|
Sign up to set email alerts
|

An Overview on Diffuse Large B-Cell Lymphoma Models: Towards a Functional Genomics Approach

Abstract: Lymphoma research is a paradigm of the integration of basic and clinical research within the fields of diagnosis and therapy. Clinical, phenotypic, and genetic data are currently used to predict which patients could benefit from standard treatment. However, alternative therapies for patients at higher risk from refractoriness or relapse are usually empirically proposed, based on trial and error, without considering the genetic complexity of aggressive B-cell lymphomas. This is primarily due to the intricate mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 159 publications
0
6
0
Order By: Relevance
“…The relatively low-cost and usability of CDX models make them attractive preclinical tools, however they typically do not fully recapitulate the disease complexity ( 134 ). CDX models are often cultured 2D over many passages in serum-containing media and implanted into immuno-compromised mice, such as NOD-SCID or Nude mice for drug efficacy studies ( 135 ). With the immune system as a crucial component of the antitumor response, and as immune-checkpoint-inhibitors (ICIs) are emerging as the standard of care for several cancer indications, this type of immuno-deficient mouse model system is not ideal for representing human biology ( 136 ).…”
Section: Patient-derived Mouse Models Of Aggressive Lymphomamentioning
confidence: 99%
“…The relatively low-cost and usability of CDX models make them attractive preclinical tools, however they typically do not fully recapitulate the disease complexity ( 134 ). CDX models are often cultured 2D over many passages in serum-containing media and implanted into immuno-compromised mice, such as NOD-SCID or Nude mice for drug efficacy studies ( 135 ). With the immune system as a crucial component of the antitumor response, and as immune-checkpoint-inhibitors (ICIs) are emerging as the standard of care for several cancer indications, this type of immuno-deficient mouse model system is not ideal for representing human biology ( 136 ).…”
Section: Patient-derived Mouse Models Of Aggressive Lymphomamentioning
confidence: 99%
“…These findings improve our understanding of the genetic underpinnings of DLBCL, which is a critical advancement in this field. The genes associated with lymphoma and chronic lymphocytic leukemia, along with their clinical significance encompassing diagnostic, prognostic, and therapeutic impacts, are compiled and presented in Letters to the Editor Table 3 [3,7,[14][15][16][17][18][19][20] with corresponding references.…”
Section: Lymphoid Neoplasm Panelmentioning
confidence: 99%
“…3 GCB DLBCL originates from B cells that have undergone germinal center reactions and typically have a better prognosis, whereas ABC DLBCL arises from B cells that have bypassed or failed to complete the germinal center reaction and often have a worse prognosis. 4 Since then, several studies have been consistent with Hans' prognostic division, while others have found no statistically significant differences between these 2 categories. 5,6 In addition, it has been examined that a high proliferation rate, as indicated by increased expression from the marker of proliferation Ki-67 (MKI67 or Ki-67) expression, is associated with poor prognosis and may be greater in the non-GCB subgroup.…”
mentioning
confidence: 93%